A new waterborne chitosan-based polyurethane hydrogel as a vehicle to transplant bone marrow mesenchymal cells improved wound healing of ulcers in a diabetic rat model. (1st March 2020) - Viezzer, Christian; Mazzuca, Rafael; Machado, Denise Cantarelli; de Camargo Forte, Maria Madalena; Gómez Ribelles, José Luis
Highlights: Membranes made of chitosan-PLGA block copolymer networks that degrade by hydrolysis in 8 weeks. Membranes that behave as hydrogels in spite of high PLGA content. The HPUC1 used in combination with bone marrow mononucleated cells are efficient in wound healing in a diabetic rat model. Abstract: Foot ulcers, a common complication of diabetes, can cause physical incapacity and are derived from several factors, including poor wound healing. New therapeutic strategies are needed to minimize this complication for the sake of patients' health. We therefore developed a new chitosan- polyurethane hydrogel membrane (HPUC) and the test results confirmed that HPUC present low cytotoxicity and improved wound healing when used with mononuclear bone marrow fraction cells in the diabetic rat model. The biodegradable hydrogels were produced in block copolymer networks with a combination of chitosan blocks and biodegradable polyurethane. The membranes were characterized by FTIR, 13 C-NMR and thermogravimetry. Swelling and hydrolytic degradation were also evaluated. The non-solubility of the membranes in good solvents and the chemical characterization confirmed that the network structure was formed between the PU and the chitosan through urea/urethane bonds. The findings confirm that the HPUC have interesting properties that make them suitable for wound healing applications.